AN ANALYSIS OF LEXICAL DENSITY AND READABILITY IN READING TEXT ON ENGLISH TEXTBOOK USED BY FORM 4 LEVEL OF SECONDARY SCHOOL STUDENTS IN SMKBSB MALAYSIA - Yulinda Pratiwi; Farikah Farikah; Lilia Indriani (Faculty of Education and Teachers Training, 2018)
English is one of the compulsory subject in Malaysian educational system. The main focus of Standar Based English Curriculum in Malaysia is focusing on the ability of students in facing the real world. The development of information also influences the students’ readiness to face the real world. The information can be obtained from any source of knowledge, such as textbook. Textbook contains many authentic materials called text. The problems arise in Sekolah Menengah Kebangsaan Bandar Sungai Buaya that the students get difficulties in reading because they have limitation on vocabulary mastery. Moreover, they also feel bored and confuse when reading a text because they do not understand the meaning of the text caused by the limitation of vocabulary and the text is too long. The objectives of this research are to analyze the number of lexical density especially lexical items and the level of readability that are found in 16 reading texts of English textbook, entitled English Form 4 that used by form 4 level of students in SMKBSB Malaysia. In conducting this research, the writer uses Lexical Density and Flesch Reading Ease